A study of residents’ ecological awareness and behaviour in the context of the transformation of Gdynia towards a zero waste city - Gwarda, Karolina (Badanie świadomości ekologicznej i zachowań mieszkańców Gdyni pod kątem realizacji idei miasta bez odpadów, 2019)
The problems of modern cities prompt the need to seek new solutions. An example of such a solution is the zero waste concept, which proposes an integrated approach to contemporary civilization changes and whose postulates perfectly fit into the specificity of cities. This includes a municipal waste management system based on the concept’s main principles, whose proper functioning rests to a large extent on the residents: they decide what will become waste, how much they will produce, and how it will be sorted. The aim of the article is to examine ecological awareness among residents and their behaviour in the context of making of Gdynia a zero waste city. A survey was conducted on the basis of a paper questionnaire, which contained statements covering the topics of knowledge, behavioural and attitude awareness, and emotional awareness. In addition was divided into three thematic areas: general ecological problems, the municipal waste management system, and consumer attitudes and behaviour. The results revealing that respondents showed a moderate level of ecological awareness
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 5, s. 123-135
Keywords: zero waste city; municipal waste management